PENGARUH VARIASI MASSA DAN TEMPERATUR AKTIVASI FLY ASH PELET DARI CANGKANG DAN SERABUT KELAPA SAWIT TERHADAP KONSUMSI BAHAN BAKAR SEPEDA MOTOR BENSIN 4 LANGKAH - Hadi Prayitno; Herry Wardono (Jurnal Ilmiah Teknik Mesin, 2014)
Energy determines the development and sustainability of economic system, social change and political growth in a country. Because of that, the energy crisis is the crisis of growth and sustainability of life system. Auto-vehicle is a certain transportation mode which an engine requiring fuel. To decrease the fuel consumption, we can use the natural resource like fly ash of shell and fiber of palm. The objective of this research is to observe the effect of the variation of mass and activation temperature in producing pelletized fly ash on performance and emission of a four-stroke petrol motorcycle. This research was done by implementing several variations of test, those were test of fuel comsumption at speed of 50km/hour for 5 km and stationer at 1500, 3500, and 5000 rpm. The fly ash used in this research was 10 mm in diameter and 3 mm in thicknes. Those fly ash were wrapped in a frame and put in an air filter of New Jupiter Z 110 cc. So the combustion air fistly contacted with the fly ash before entering into the combustion chamber. From the results, the best fly ash mass used P•—nƒì ?‡ and the best temperature activation is 175 oC. Those fly ash can save the fuel consumption by 17.23 % (road test) and 20.06% (stasioner test). Keywords : fly ash adsorbent, combustion air treatment, emission